Continuous glucose monitoring (CGM) using lab on chip (LOC) [electronic resource] - Nurul Atirah Mustaffa, 1992- (Johor Bharu Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2015